SignedLogWeight Plus

Let w1 = (s1, x1) and w2 = (s2, x2) be two elements of {-1,1} X [-∞, ∞].

Let z1 = s1 e-x1 and z2 = s2 e-x2.

Then w1 ⊕ w2 = (sgn(z1+z2), -log e-|z1+z2|).

-- MichaelRiley - 19 Oct 2010

Topic revision: r1 - 2010-10-19 - MichaelRiley
 
This site is powered by the TWiki collaboration platform Powered by PerlCopyright © 2008-2017 by the contributing authors. All material on this collaboration platform is the property of the contributing authors.
Ideas, requests, problems regarding TWiki? Send feedback